2009
DOI: 10.1227/01.neu.0000339115.12803.4e
|View full text |Cite
|
Sign up to set email alerts
|

Use of Temozolomide in Aggressive Pituitary Tumors

Abstract: The marked improvement in clinical state of the first 2 patients accompanied by radiological evidence of tumor shrinkage in all patients demonstrates the potential use of temozolomide in treating aggressive pituitary macroadenomas. The usefulness of temozolomide in aggressive pituitary adenomas should be studied in larger trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 17 publications
0
67
0
1
Order By: Relevance
“…These included tumor necrosis and hemorrhage, 15,23 tumor degenerative and cystic changes, 22 and tumor shrinkage. 2,10,11,14,[19][20][21]24 These changes could be observed as early as 2 months after the onset of temozolomide treatment.…”
Section: Morphologic Changesmentioning
confidence: 97%
See 3 more Smart Citations
“…These included tumor necrosis and hemorrhage, 15,23 tumor degenerative and cystic changes, 22 and tumor shrinkage. 2,10,11,14,[19][20][21]24 These changes could be observed as early as 2 months after the onset of temozolomide treatment.…”
Section: Morphologic Changesmentioning
confidence: 97%
“…Fully 10 more patients with pituitary adenomas have received treatment with temozolomide 2,10,11,14,19,20,22 (unpublished results), bringing the current total to 13 patients, including 9 men and 4 women ages 20 to 61 years (mean, 47.9 years) ( Table 2). Aside from 1 incidentally discovered tumor in a patient with concomitant glioblastoma multiforme, all tumors have been studied morphologically.…”
Section: Pituitary Adenomasmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TMZ clinical trials have been performed to test its activity against brain metastatic solid tumors, leukemia (8), pancreatic neuro endocrine tumors (9) and refractory pituitary adenomas (10)(11)(12)(13)(14). Two case studies related to gonadotroph adenoma patients report that their lesions decreased after TMZ therapy (15,16), and studies of TMZ on MMQ, GH3, and AtT20 cell lines suggested that this drug may have efficacy in pituitary adenoma cells (17 to attain biochemical control in a severe case of acromegaly (18).…”
Section: Introductionmentioning
confidence: 99%